Impact of the Auditory, Intellectually, and Repetition (AIR) Learning Model on Students’ Mathematical Critical Thinking - Indah Natalia Harefa; Yakin Niat Telaumbanua; Ratna Natalia Mendrofa; Netti Kariani Mendrofa (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Critical thinking is an essential skill in 21st-century mathematics education; however, Indonesian students still demonstrate low achievement in this domain. Preliminary observations at SMP Negeri 8 Gunungsitoli revealed that students’ mathematical critical thinking skills were not yet optimal, partly due to the predominance of conventional instructional approaches. This study examined the effect of the Auditory, Intellectually, and Repetition (AIR) learning model on students’ mathematical critical thinking skills. A quasi-experimental method with a nonequivalent control group design was employed, involving 60 seventh-grade students divided into an experimental group (n = 30) and a control group (n = 30). The research instrument was an essay-based mathematical critical thinking test consisting of three items, which demonstrated logical and empirical validity and satisfactory reliability. The results indicated that both groups had relatively comparable low baseline performance. After the intervention, the experimental group achieved a mean score of 71.80 (high category), whereas the control group reached only 39.80 (low category). An independent-samples t-test showed that t = 10.683 exceeded ttable = 1.672 (p < 0.05), with a very large effect size (Cohen’s d = 2.76). Simple linear regression analysis indicated that the AIR model accounted for 88.6% of the variance in students’ mathematical critical thinking skills (R² = 0.886). These findings confirm that the AIR learning model effectively enhances mathematical critical thinking by engaging students in listening activities, reflective intellectual processing, and repeated practice. This study contributes theoretically to the development of higher-order thinking-oriented mathematics instruction and offers practical implications for teachers and policymakers in promoting interactive, student-centered learning models.